Strategi Dakwah Klinik Nikah Kota Binjai Dalam Mengedukasi Generasi Muda Binjai Utara Tentang Fikih Pernikahan - Bustamam Prasetyo; Zulkarnain Abdurrahman (STAI Bumi Silampari, 2025)
The state of the younger generation presents a considerable challenge in terms of a good understanding of the fiqh of marriage. Many of them are influenced by cultural circumstances and lack a strong foundation. This study aims to explore the challenges faced by the Binjai City Nikah Clinic in carrying out marriage proselytization to the younger generation, as well as identifying strategies and solutions implemented to overcome these challenges. This research is a field research using qualitative methods with in-depth interviews with Nikah Clinic managers and program participants. The findings show that the main challenges faced include a lack of understanding about marriage education, changes in social values that are more liberal, and the influence of secular and materialistic views that are getting stronger. In addition, there is a tendency among the younger generation to postpone marriage. To overcome these challenges, the Marriage Clinic implemented several strategies, including improving the quality and relevance of programs such as pre-marital lectures that focus on mental and emotional readiness, as well as organizing seminars and workshops that teach practical skills in managing home life. The Marriage Clinic also applies a more personalized approach of mentoring and small group discussions, and invites the community to be more involved in da'wah and marriage education. The effectiveness of these strategies is evident in the participants' increased understanding of the importance of marriage readiness, although major challenges remain in relation to the habits and views of the younger generation towards marriage.